Tourist technological engagement through mobile services at destination - Mohd, Nur Shuhadah; Ismail, Hairul Nizam; Isa, Norliza; Syed Jaafar, Syed Muhammad Rafy (2019)
Mobile utilisation had dictated tourist on-site travel consumption and psychologically altering the way tourist experience destination. Mobile services was seen as a mediator in tourist-destination encounter, enabling tourist to glimpse space in slightly different perspective. The high dependency on mobile services, especially among the new tourist generation, was presumed to be influential in igniting curiosity and imposing emotional impact. The distinction of experience obtained from techengagement alter the current structure of experience and constructing new form of technology mediated travel experience that constitute of technology-emotion relation. Particularly, their enjoyment towards this human-technology engagement in mediating the destination encounter is believed to be the antecedent of the overall travel satisfaction. Therefore, perspective on tourist on-site mobile utilization pattern is important in further understanding the technology mediated travel experience. Information pertaining tourist spatial technological engagement was collected in understanding its influence on travel experience. Millennial generation was specified as the target group since they hold the demand of current tourism industry. On-going questionnaire survey of 221 respondents was conducted on 55 identified main attractions within Kuala Lumpur city centre. Preliminary findings reveals that tourist perceived influence of mobile engagement does varies based on places within the destination. This is an early evidence that technology mediated travel experience does lead to development of emotional experience and improves destination interaction.